(untitled) (International Journal of Engineering and Computer Science, 2018)
The future demands the solutions to be mobile and portable for their widespread use and effectiveness. Ubiquitously the Internet gets most of the traffic from portable devices. Hence there is a need for Professional Communication and recruitment to go mobile. This paper intends to throw light on ProfsApp which is a light weight Professional Networking App that simplifies employee referral, standardizes and enhances professional communication.